2006
DOI: 10.1097/01.wnp.0000228514.40227.12
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Yield of EEG

Abstract: The EEG is the most common neurodiagnostic test performed to evaluate patients with suspected seizures. The majority of EEGs are requested in patients because of suspected seizures or for seizure management. It is unlikely that the patient's usual spell will be recorded during a routine EEG. Therefore, several activation techniques have been used in clinical EEG to help increase the occurrence of interictal epileptiform abnormalities, which are highly correlated with the diagnosis of a seizure disorder. EEG la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 56 publications
3
46
0
3
Order By: Relevance
“…7 Similarly, in other reports that compared patients who have epilepsy with and without intracranial tumors, the activation of focal interictal activity during routine EEG was demonstrated in 6% to 9% of patients following HV. 8,9 In the study by Gabor et al, the subpopulation of patients defined by focal discharges on EEG showed an activation effect by HV in 6% of patients. 10 Compared to our study, the above reports demonstrated a relatively higher number of events during HV.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…7 Similarly, in other reports that compared patients who have epilepsy with and without intracranial tumors, the activation of focal interictal activity during routine EEG was demonstrated in 6% to 9% of patients following HV. 8,9 In the study by Gabor et al, the subpopulation of patients defined by focal discharges on EEG showed an activation effect by HV in 6% of patients. 10 Compared to our study, the above reports demonstrated a relatively higher number of events during HV.…”
Section: Discussionmentioning
confidence: 97%
“…6,8 One needs to be aware of the appearance of HV-induced high-amplitude rhythmic slowing with altered awareness, which mimic absence seizures but are a different and characteristic EEG finding. 13 Similarly, overinterpretation of EEG during HV is well recognized, as reported by Benbadis and Tatum.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, this adenosine tone can also be reduced by hypocapnia, which promotes seizure activity in hippocampal slices (Dulla et al, 2005). The fact that hyperventilation-induced hypocapnia is used to provoke seizures as a diagnostic test (Mendez and Brenner, 2006) and enhance electroconvulsive seizures, as are A1 receptor antagonists such as caffeine, theophylline and aminophylline (Loo et al, 2010), strongly suggests an important tonic inhibitory role for endogenous adenosine in the regulation of human seizures. Moreover, successful attempts to terminate human epileptic seizures, even after their initiation, have been made using 5 % CO2 inhalation (Tolner et al, 2011).…”
Section: Insight Into the Regulation Of Basal And Seizure-induced Purmentioning
confidence: 99%
“…EEG is mainly used in repeated brief recordings, typically lasting 20 minutes, resulting in short samples for assessing brain functions in disease and especially in epilepsy Mendez and Brenner, 2006;Noachtar and Rémi, 2009). However, there is an increased use of long-term EEG monitoring (LTM), lasting hours or days, often with synchronous video recording.…”
Section: General Introductionmentioning
confidence: 99%